Immunohistological recognition of cyclin D1 expression by non‐lymphoid cells among lymphoid neoplastic cells. Issue 3 (12th June 2013) - Abdulla, Zainalabideen; Turley, Helen; Gatter, Kevin; Pezzella, Francesco
<x xml:space="preserve">Abstract</x> Cyclin D1 immunostaining of non‐neoplastic cells has been a source of diagnostic confusion especially in lymphoproliferative lesions. This study has reviewed these in two hundred and thirty‐one haematopathological samples stained for cyclin D1. Most cases were formalin‐fixed except for a few bone marrow trephines, which were B‐5 fixed, and EDTA decalcified. Overall, 94% (216/231) of cases showed one or more types of non‐neoplastic cells expressing Cyclin D1 of variable intensity. Endothelial cells and histiocytes were the most commonly identified Cyclin D1 positive cells being positive in 92% (214/231) of cases. Other normal cell types identified included fat cells, stromal fibroblasts, glial cells, spermatocytes, smooth muscle cells, osteoblasts and where present epithelial cells. Many normal cell types can express cyclinD1. Knowledge of these is useful to prevent misinterpretation of cyclin D1 positive tumours.